2016
DOI: 10.1007/s00138-016-0776-4
|View full text |Cite
|
Sign up to set email alerts
|

Pupil detection for head-mounted eye tracking in the wild: an evaluation of the state of the art

Abstract: Robust and accurate detection of the pupil position is a key building block for head-mounted eye tracking and prerequisite for applications on top, such as gaze-based human-computer interaction or attention analysis. Despite a large body of work, detecting the pupil in images recorded under real-world conditions is challenging given significant variability in the eye appearance (e.g., illumination, reflections, occlusions, etc.), individual differences in eye physiology, as well as other sources of noise, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 34 publications
0
74
0
2
Order By: Relevance
“…This is in stark contrast to remote eye tracking, where several studies have called attention to the characterization of eye-tracking data quality (Blignaut & Wium 2014;Wass, Forssman, & Leppänen, 2014;Nyström, Andersson, Holmqvist, & van de Weijer, 2013;Hessels, Andersson, Hooge, Nyström, & Kemner, 2015), with some studies specifically examining data quality using a series of tests mimicking participant behavior during typical recording sessions (Hessels, Cornelissen, Kemner, & Hooge, 2015;Niehorster, Cornelissen, Holmqvist, Hooge, & Hessels, 2018). Although it has been established that eye camera positioning and illumination conditions can greatly influence tracking quality in head-worn eye tracking (Świrski, Bülling, & Dodgson, 2012;Tonsen, Zhang, Sugano, & Bülling, 2016;Fuhl, Tonsen, Bülling, & Kasneci, 2016), to the best of the authors' knowledge, only a single study has actually empirically compared the accuracy and precision of multiple head-worn eyetracking setups-yet the study (MacInnes, Iqbal, Pearson, & Johnson, 2018) was limited in scope to the ideal case of careful calibration and evaluation immediately thereafter. It is therefore not representative of how these eye-tracking setups are often used with unconstrained participants in uncontrolled environments.…”
Section: Introductionmentioning
confidence: 99%
“…This is in stark contrast to remote eye tracking, where several studies have called attention to the characterization of eye-tracking data quality (Blignaut & Wium 2014;Wass, Forssman, & Leppänen, 2014;Nyström, Andersson, Holmqvist, & van de Weijer, 2013;Hessels, Andersson, Hooge, Nyström, & Kemner, 2015), with some studies specifically examining data quality using a series of tests mimicking participant behavior during typical recording sessions (Hessels, Cornelissen, Kemner, & Hooge, 2015;Niehorster, Cornelissen, Holmqvist, Hooge, & Hessels, 2018). Although it has been established that eye camera positioning and illumination conditions can greatly influence tracking quality in head-worn eye tracking (Świrski, Bülling, & Dodgson, 2012;Tonsen, Zhang, Sugano, & Bülling, 2016;Fuhl, Tonsen, Bülling, & Kasneci, 2016), to the best of the authors' knowledge, only a single study has actually empirically compared the accuracy and precision of multiple head-worn eyetracking setups-yet the study (MacInnes, Iqbal, Pearson, & Johnson, 2018) was limited in scope to the ideal case of careful calibration and evaluation immediately thereafter. It is therefore not representative of how these eye-tracking setups are often used with unconstrained participants in uncontrolled environments.…”
Section: Introductionmentioning
confidence: 99%
“…Short trial durations and repeated stimulus display in a laboratory setting is likely to lead to highly similar scanpaths and few noise. On the other hand, real-world experiments are always associated with a high level of pupil detection failures (a review can be found in Fuhl et al (2016)) and identical experimental conditions are hard to reproduce (e.g., the same amount traffic while driving). Scanpaths of such experiments are likely to be more dissimilar and noisy.…”
Section: Experimental Settings and Datamentioning
confidence: 99%
“…Therefore, by using a visible light, we also explore a human eye-computer interaction system. Recently, pupil detection methods are evaluated [10]. In the future, we investigate methods described in the paper [10].…”
Section: Resultsmentioning
confidence: 99%